Impacts of disability on daily travel behaviour: A systematic review. Issue 2 (4th March 2023) - Park, Keunhyun; Esfahani, Hossein Nasr; Novack, Valerie Long; Sheen, Jeff; Hadayeghi, Hooman; Song, Ziqi; Christensen, Keith
ABSTRACT: While people with disabilities have different travel patterns compared with the general traveller population, such discrepancies are ignored in mainstream travel demand modelling and planning practice. The failure to represent the diverse travel behaviour of people with disabilities leads to inaccurate forecasting and poor decision-making and exacerbates transportation disadvantages. Thus, this systematic review synthesises previous studies of travel behaviours among people with disabilities, differing from people without disabilities, in terms of trip frequency, mode choice, travel time and distance, and barriers. This review identified 115 peer-reviewed studies of the daily travel patterns of individuals across three categories of disabilities—mobility, cognitive, and sensory. Our review reveals that persons with disabilities make 10–30% fewer trips than those without disabilities, particularly non-work trips. Another significant difference is in travel mode choice—increased uses of public transit and taxi and riding with others and decreased walking and driving among those with disabilities. People with disabilities are prone to utilising slower means of transportation and travelling shorter distances. The quantitative review highlighted a limited considertation of the built environment characteristics and temporal factors as travel behavour predictors. Further, our qualitative review shows that despite a high level of adaptation, persons with disabilities encounter many barriers in the built environment to their transportation access. The environmental, social, and system barriers make specific modes unavailable to travellers with disabilities, increase travel time, and eventually decrease their trip frequency. This paper provides implications for travel demand modelling and urban and transportation planning and policy that better supports the transportation needs of persons with disabilities.